Skeleton man ebook - Bruchac, Joseph (2009)
A chilling middle grade novel featuring a brave young girl, missing parents, and a terrifying stranger, based on a Native American legend. R.L. Stine, New York Times bestselling author of the Goosebumps series, raved, "This book gave ME nightmares!" Molly's father, who grew up on the Mohawk Reserve of Akwesasne, always had the best scary stories. One of her favorites was the legend of Skeleton Man, a gruesome tale about a man with such insatiable hunger he ate his own flesh before devouring those around him. But ever since her parents mysteriously vanished, those spooky tales have started to feel all too real. Don't miss The Legend of Skeleton Man: a spine-tingling collection of Skeleton Man and its sequel, The Return of Skeleton Man!